2019
DOI: 10.1111/cei.13390
|View full text |Cite
|
Sign up to set email alerts
|

Secretory IgA accumulated in the airspaces of idiopathic pulmonary fibrosis and promoted VEGF, TGF-β and IL-8 production by A549 cells

Abstract: Summary Secretory IgA (SIgA) is a well‐known mucosal‐surface molecule in first‐line defense against extrinsic pathogens and antigens. Its immunomodulatory and pathological roles have also been emphasized, but it is unclear whether it plays a pathological role in lung diseases. In the present study, we aimed to determine the distribution of IgA in idiopathic pulmonary fibrosis (IPF) lungs and whether IgA affects the functions of airway epithelial cells. We performed immunohistochemical analysis of lung sections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Some studies have shown that SIgA can bind to the surface of A549 cells. A549 is usually used as a cell line with AT2 cell phenotype in vitro experiments, which can promote the production of vascular endothelial growth factor (VEGF), and transforming growth factor (TGF)‐β [ 83 ]. Notably, these cytokines are involved in the pathogenesis of IPF [ 84 86 ].…”
Section: The Relationship Between Siga and Pulmonary Diseasesmentioning
confidence: 99%
“…Some studies have shown that SIgA can bind to the surface of A549 cells. A549 is usually used as a cell line with AT2 cell phenotype in vitro experiments, which can promote the production of vascular endothelial growth factor (VEGF), and transforming growth factor (TGF)‐β [ 83 ]. Notably, these cytokines are involved in the pathogenesis of IPF [ 84 86 ].…”
Section: The Relationship Between Siga and Pulmonary Diseasesmentioning
confidence: 99%
“…Equipped with less receptors but still responsive to IgA are neutrophils, dendritic cells, macrophages, basophils and even epithelial lining cells that express the transferrin receptor such as alveolar-type 2 cells (170). An additional, so far unidentified receptor is present on M cells (microfold cells) (171,172).…”
Section: The Role Of Secretory Iga In Epithelial Defensementioning
confidence: 99%
“…The comparison of the EBC cytokine concentrations between nontreated patients with IPF and controls showed a significantly higher EBC concentration of IL-8 in the latter. This is a rather unexpected finding, as it is not in line with earlier observations that almost uniformly support the involvement of IL-8 as a promoter of fibrogenesis [28][29][30]. Elevated serum concentrations of IL-8 were found in patients with IPF compared to controls by Ziora et al [4].…”
Section: Discussionmentioning
confidence: 64%